Jak funkcjonuje moralność? Wybory moralne a wartości chrześcijańskie - Kraj, Tomasz (Teologia i Moralność, 2020)
Knowledge of the moral teaching of the Roman Catholic Church is generally scarce, even among believers. This situation contributes to numerous misunderstandings concerning the Church’s position within the public debates of new proposals like IVF or sexual morality (eg. the LGBT movement). It seems to outsiders that the Church’s standpoint is based on some old and outdated convictions incomprehensible for people today. Meanwhile for the Church, which is concerned with the overall well-being of each man, this well-being is the main reason for its viewpoint and teaching. Although the Church’s explanation is not based exclusively on philosophical reasons (i.e. based on human reason and thus intelligible for all people of good will) these reasons play an important role in the dialogue between the Church and the contemporary world. One of the Church’s most important rationales refers to the concept of human personal fulfilment and basic human goods.